KECEMASAN IBU YANG MEMILIKI REMAJA PUTRI PENDERITA SKIZOFRENIA - Mai Darni; Sulastri Sulastri (Jurnal Psikologi Malahayati, 2019)
ANXIETY AMONG MOTHERS OF DAUGHTER WITH SCHIZOFRENIAIntroduction: Schizofrenia is a severe mental dirsorder. Adolescence with schizofrenia can be a tough challanger for the parents. Problems in adolescnece with schizofrenia can be a souce of anxiety especially for mothers.Purpose: This study aims to describe the anxiety in mothers who have young women who suffer from schizophrenia. The subjects in this study were two mothers who had young teenagers with schizophrenia.Methods: The location of the research was in the Bandar Lampung region. The study was conducted using qualitative methods with methods of collecting data on interviews, observation and documentation.Results: Based on the results of data analysis it can be concluded that there is anxiety in both respondents in accompanying their young women. The source of anxiety in the first respondent was anxiety because of the pain suffered by the respondent's child, education, future and additional anxiety and in the second respondent who was the source of anxiety was illness, education being taken by the respondent's daughter, and the future. The first respondent with a source of pain, future anxiety, education and the presence of additional anxiety was sufficient to overcome his anxiety after nearly seven years accompanying his daughter. One of the factors is the condition of her daughter who gradually improved, this can be seen from the daughter of the respondent who has been able to carry out daily activities. The second respondent with a source of pain, education and future anxiety still looks anxious, this can be caused either by the condition of his unstable daughter.Conclusion: Mothers of adolescence with schizofrenia found to be having anxiety.Pendahuluan: Skizofrenia merupakan gangguan mental yang berat. Remaja penderita skizofrenia menjadi tantangan besar bagi orang tua.  Permasalahan pada remaja skizofrenia dapat menimbulkan kecamasan khususnya kepada ibu sebagai pengasuh utama.Tujuan: Penelitian ini bertujuan untuk mengetahui gambaran kecemasan pada ibu yang memiliki remaja putri yang menderita skizofrenia.Metode: Subjek dalam penelitian ini adalah dua orang ibu yang memiliki remaja putrid penderita skizofrenia. Lokasi yang menjadi tempat penelitian adalah di wilayah Bandar Lampung.Penelitian dilakukan dengan menggunakan metode kualitatif dengan metode pengumpulan data wawancara, observasi dan dokumentasi.Hasil: Berdasarkan hasil analisis data dapat disimpulkan bahwa terdapat kecemasan pada kedua responden dalam mendampingi remaja putri mereka. Sumber kecemasan pada responden pertama adalah kecemasan karena sakit yang di derita anak, pendidikan, masa depan dan kecemasan tambahan dan pada responden kedua yang menjadi sumber kecemasan adalah sakit, pendidikan yang sedang ditempuh putri responden, dan masa depan. Responden pertama dengan sumber kecemasan sakit, masa depan,pendidikan dan adanya kecemasan tambahan cukup mampu mengatasi kecemasannya setelah hampir tujuh tahun mendampingi putrinya. Salah satu yang menjadi faktornya adalah kondisi putrinya yang berangsur membaik, hal ini bisa terlihat dari putri responden yang telah bisa melakukan aktivitas sehari-hari. Responden kedua dengan sumber kecemasan sakit, pendidikan dan masa depan masih terlihat kecemasannya, hal ini bisa disebabkan salah satunya karena kondisi putrinya yang belum stabil.Simpulan: Ibu yang memiliki anak penderita skizofrenia ditemukan mengalami kecemasan.